Lektur dan Khazanah Keagamaan: Prospek Pengembangannya - Choirul Fuad Yusuf (Jurnal Lektur Keagamaan, 2012)
Religious literature and heritage (RLH) plays an important and strategic role in nearlu all aspects of the nation. Politically, respecting RLH as a part of the cultural legacy, besides strengthening nationalism, it will be functional for upholding our prestige and dignity. RLH acknowledges our past cultural legacies, nobilty and worth to be revitalized for the future life betterment. Further, historically, or course RLH is very strategic to be a medium for connecting the past, present and next generation. In this context, understanding of what RLH is in essence becomes something necessary for the people. For this purpose, the article tries epistemologically to describe, unpack, elaborat, and detail “what, why and how RLH” have to be conserved and managed for the sake of strengthening the nation in the frame of global dynamics.